Standardization of irrigation and fertigation schedules for optimizing flower yield, water use efficiency and economic returns in chrysanthemum (Chrysanthemum morifolium Ramat.) cultivars under semi-arid conditions - Gouthami, B.; Gurjar, D. S.; Brahmanand, P. S.; Tiwari, A. K.; Singh, Mam Chand; Babu, Subhash; Prasad, Shiv; Rajput, Jitendra (Frontiers in Agronomy, 2025)
Understanding the effects of irrigation levels and nutrient levels on crop production is crucial for the advancement of sustainable agriculture, encompassing crop growth management, soil health preservation, and the strategic use of the input resources. Therefore, this study assessed the impact of different irrigation and fertigation management practices on yield, water use efficiency (WUE), and economic feasibility of chrysanthemum (Chrysanthemum morifolium Ramat.) cultivars. The field experiments were carried out during the rabi seasons of 2023–24 and 2024–25 at the Precision Farming Development Centre (PFDC), Water Technology Centre, ICAR-Indian Agricultural Research Institute, New Delhi. A split-split plot design was adopted, incorporating three experimental factors: two chrysanthemum cultivars (Autumn Pink and Autumn White), three irrigation regimes (0.5 Epan, 0.75 Epan, and 1.0 Epan), and three fertigation levels (50%, 75%, and 100% of the recommended fertilizer dose). The results revealed that the Autumn White cultivar consistently outperformed Autumn Pink cultivar in terms of flower yield, WUE, and economic returns. Among different irrigation regimes, the highest WUE was observed in 0.75 Epan irrigation level treatment. Similarly, the highest fertigation level (100% RDF) produced the best results in terms of yield and economic benefits. Economic analysis showed that the treatment combination V2I2F3 (Autumn White + Irrigation at 0.75 Epan + 100% RDF) consistently achieved the higher gross returns, net returns, and profitability across both years and pooled data. This study concludes that optimizing irrigation and fertigation strategies, particularly for commercial chrysanthemum cultivars, can significantly improve profitability and sustainability, especially in water-scarce regions.